Actual changes in system of urban planning in post-socialist city: the case of Prague. Issue 4 (1st October 2016) - Landa, Filip
Abstract: After the change of political system in Czechoslovakia (1989) came also a lot of social, economical and cultural changes. Today, all the Czech cities stay in front of the biggest change of city planning philosophy in last two decades. Prague, the capital city of Czech Republic, decided for a big institutional transition in 2012. The municipality, in cooperation with Faculty of Architecture CTU in Prague, is preparing completely pioneering methodology for quality commissioning of land use plans and, in cooperation with the new Institute of Planning and Development, is preparing innovative system of city planning. There are new ordinances, laws, regulations, tourist trade strategies and many other documents. Prague, as one of the strongest regions in East-Central Europe, can be seen like a laboratory of current development of post-socialist city. The new methodology of Metropolitan Plan could be a key to success.